Outcomes of complex robot-assisted extravesical ureteral reimplantation in the pediatric population. Issue 3 (June 2016) - Arlen, Angela M.; Broderick, Kristin M.; Travers, Curtis; Smith, Edwin A.; Elmore, James M.; Kirsch, Andrew J.
Summary: Introduction and objective: While open ureteral reimplantation remains the gold standard for surgical treatment of vesicoureteral reflux (VUR), minimally invasive approaches offer potential benefits. This study evaluated the outcomes of children undergoing complex robot-assisted laparoscopic ureteral reimplantation (RALUR) for failed previous anti-reflux surgery, complex anatomy, or ureterovesical junction obstruction (UVJO), and compared them with patients undergoing open extravesical repair. Study design: Children undergoing complex RALUR or open extravesical ureteral reimplantation (OUR) were identified. Reimplantation was classified as complex if ureters: 1) had previous anti-reflux surgery, 2) required tapering and/or dismembering, or 3) had associated duplication or diverticulum. Results: Seventeen children underwent complex RALUR during a 24-month period, compared with 41 OUR. The mean follow-up was 16.6 ± 6.5 months. The RALUR children were significantly older (9.3 ± 3.7 years) than the OUR patients (3.1 ± 2.7 years; P < 0.001). All RALUR patients were discharged on postoperative day one, while 24.4% of children in the open group required longer hospitalization (mean 1.3 ± 0.7 days; P = 0.03). Adjusting for age, there was no significant difference in inpatient analgesic usage between the two cohorts. Three OUR patients (7.3%) developed postoperative febrile urinary tract infection compared with a single child (5.9%) undergoing RALUR ( P = 1.00). There was no significant difference in complication rate between the two groups (12.2% OUR versus 11.8% RALUR; P = 1.00). A postoperative cystogram was performed in the majority of RALUR patients, with no persistent VUR detected, and one child (6.7%) was diagnosed with contralateral reflux. Discussion: Reported VUR resolution rates following robot-assisted ureteral reimplantation are varied. In the present series, children undergoing RALUR following failed previous anti-reflux surgery, with complex anatomy, or UVJO experienced a shorter length of stay but had similar analgesic requirements to those undergoing open repair. Radiographic, clinical success rates and complication risk were comparable. This study had several limitations, aside from lack of randomization. Analgesic use was limited to an inpatient setting, and pain scores were not assessed. Not all children underwent a postoperative VCUG, so the true radiographic success rate is unknown. A larger patient cohort with longer follow-up is necessary to determine predictors of radiographic and clinical failure. Conclusion: Older children with a previous history of anti-reflux surgery were more likely to undergo RALUR. These children had success and complication rates comparable to younger patients following complex open extravesical reimplantation, which underscores the expanding role of robot-assisted lower urinary tract reconstructive surgery in the pediatric population.